More accurate than assumed: Learners' metacognitive beliefs about the effectiveness of retrieval practice. (February 2023) - Weissgerber, Sophia C.; Rummer, Ralf
Abstract: We doubt the prevailing interpretation of lower Judgments of Learning (JOLs) for testing over rereading to reflect learners' favoritism of an ineffective activity. We argue that JOLs for testing are biased due to a negative feedback effect. In three preregistered experiments ( N final  = 306), we eliminated the feedback effect by asking students to only imagine learning with the described activities (rereading/testing) after reading a text and by capturing offline-JOLs ( off-JOLs  = being decoupled from the current learning experience) as a function of an imaginary final test delay (5 min/1 week/2 weeks). In 5-min conditions, off-JOLs consistently reflected no differences between rereading and testing; in 1-week and 2-week conditions, two (of three) experiments demonstrated an advantage of testing over rereading. These results are consistent with actual learning outcomes in an experiment using the same text and activities (Rummer et al., 2017, Exp. 1). Learners' metacognitive judgments resembled actual learning outcomes more accurately than suggested by previous research. Highlights: Judgments of Learning (JOLs) are biased by a negative feedback effect of testing. Offline-Judgments of Learning (off-JOLs) are less biased metacognitive measurements. Off-JOLs are measured independently of the current learning experience. Off-JOLs do not show an overestimation of rereading's effectiveness over testing. Off-JOL for testing more accurately reflected actual learning outcomes.